ANALISIS TINDAK TUTUR ILOKUSI UJARAN KEBENCIAN PADA ETNIS TIONGHOA DALAM PUTUSAN MAHKAMAH AGUNG REPUBLIK INDONESIA - Hafit, Muhammad Abu (Jurnal Komposisi, 2023)
This study describes the types and functions of hate speech against ethnic Chinese in the decisions of the Supreme Court of the Republic of Indonesia. The research method uses descriptive qualitative. Data collection uses the method of observing and noting. The results of the study show that there are types and functions of illocutionary speech acts in the form of assertive types as many as 5 data functions stating as many as 5 data. The directive type is 5 data, the function invites 4 data and challenges 1 data. The type of commissive as much as 2 data function threatens as much as 2 data. There are 9 types of expressive functions that insult or criticize as many as 9 data. The most common types and functions of expressive speech acts are due to the fact that in hate speech utterances place more emphasis on the psychological condition of the speaker in uttering or expressing his situation or what the speaker is feeling.